Executive Carriages Toilet of Joglosemarkerto Indonesian`S Train Using Universal Design Approach - Akh. Sokhibi; Bambang Suhardi; Pringgo Widyo Laksono; Sugiono Sugiono (Journal of Applied Engineering and Technological Science)
This study aims to assess the accessibility of toilets on the Joglosemarkerto executive train for people with disabilities, especially wheelchair users, using the Universal Design approach. The research method is a mixed method, through direct measurement of toilet dimensions, accessibility checklists based on universal design principles, and online user perception surveys involving 64 respondents, including disabled groups. The Accessibility Index is calculated based on weighting the door, sink, and main toilet room. The study results indicate that the accessibility index category is low, with a score of 22 for the toilet door, 17.5 for the sink, and 24.4 for the main toilet room. The main obstacles are narrow circulation space, insufficient door width, information in Braille, and emergency buttons not being available. Practically, this study encourages operators and policymakers to improve the design of accessible train toilets by involving disabled groups in the design. Theoretically, this study enriches the literature on evaluating public transportation accessibility in Indonesia through the presentation of a replicable universal design evaluation model. The contribution of this study is to map the infrastructure gaps and develop recommendations to improve the inclusiveness of railways in Indonesia and promote equality of access.